Extreme prematurity in a public reference unit: morbidity, viability and mortality (Research, Society and Development, 2022)
Premature birth is a public health problem due to the high mortality rate associated and risk of severe disabilities throughout life. The objective was to evaluate the morbidity and mortality in a high-risk maternity hospital and knowing the threshold of viability. The sample was selected in four stages: identification, selection, stratification of preterm infants by gestational age and birth weight, and structured data collection. Neonates up to 31 weeks of gestational age who had a death outcome were evaluated from August 2015 to August 2020 through a retrospective survey based on the descriptive analysis of variables related to pregnancy, childbirth, and the newborn. Absolute and relative percentages were described for the categorical variables and calculated mean, median and standard deviation, minimum and maximum value for continuous quantitative variables. Most newborns had a small gestational age (56.3%), extremely low birth weight (39.8%), and presented with asphyxia (38.7%). The main morbidities were respiratory distress syndrome (100%) and sepsis (40.6%). The overall mortality rate was 55.9% from 26% at 31 weeks to 100% at 22 weeks; most deaths (56.3%) occurred between 22 and 27 weeks. Of the 266 deaths, 25 (9.3%) still occurred in the delivery room and 237 (89%) in the neonatal unit. The early mortality rate was 0.77 deaths per 1,000 live births, and the late mortality rate was 0.22 deaths per 1,000 live births. Viability’s limit found was 28 weeks. Death, in addition to fetal characteristics, was influenced by a series of modifiable risk factors.